2016
DOI: 10.1039/c6ra11737f
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Heck reaction catalyzed by Pd nanoparticles immobilized on DNA-modified MWCNTs

Abstract: This is the first report of regioselective Heck reaction of aryl iodides with 2,3-dihydrofuran using heterogonous nanocatalyst. Herein, palladium nanoparticles is immobilized on DNA-modified multi walled carbon nanotubes and characterized by FT-IR spectroscopy, UV-vis spectroscopy, field emission scanning electron microscopy, X-ray diffraction, transmission electron microscopy, inductively coupled plasma and elemental analysis. DNA as a welldefined structure and biodegradable natural polymer generate the palla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 63 publications
1
17
0
Order By: Relevance
“…Another strategy to immobilize and stabilize Pd NPs was developed by the Hajipour research group and consisted of using less expensive and commercially available natural DNA . This molecule has several properties, such as solubility and biodegradability, that make it a very suitable scaffold for designing a hybrid catalyst .…”
Section: Carbon Nanotubesmentioning
confidence: 99%
“…Another strategy to immobilize and stabilize Pd NPs was developed by the Hajipour research group and consisted of using less expensive and commercially available natural DNA . This molecule has several properties, such as solubility and biodegradability, that make it a very suitable scaffold for designing a hybrid catalyst .…”
Section: Carbon Nanotubesmentioning
confidence: 99%
“…[49][50][51] The high activity of MNP@PAMAM-Co is probably due to good dispersion of cobalt nanoparticles and good synergistic effects of cobalt nanoparticles with ligands that are grafted on MNP. The first step of this catalytic coupling reaction is oxidative addition, so the reactivity of C-halogen bond has definite influence.…”
Section: Performance Of the Catalyst On Several Substrates For Mizomentioning
confidence: 99%
“…Therefore, to overcome these problems more convenient approaches utilizing cobalt catalyst are required. Because of our continued interest in applying cobalt catalyst in coupling reactions, [5][6][7][8][9] we found that it can be used as a highly efficient catalyst for a threecomponent coupling reaction of aldehyde, alkyne, and amine and Sonogashira coupling reaction in green media and mild reaction conditions. Activation of a terminal alkyne C-H bond by transition metal catalysts is an interest reaction in organic synthesis.…”
Section: Introductionmentioning
confidence: 99%